2020
DOI: 10.21037/jtd-20-1546
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Type D Personality pattern on prehospital delay in patients suffering from acute myocardial infarction

Abstract: Background: The Type D Personality (TDP) has been specifically linked to acute myocardial infarction (AMI). However, the impact on prehospital delay of AMI patients is unclear. The aim of this study was to assess the relationship between TDP and pre-hospital delay time (PHT) in a Chinese population. Methods: A total of 256 AMI patients (47 women and 209 men) were taken from the Multicenter Delay in Patients Experiencing AMI in Shanghai (MEDEA FAR-EAST) study. Sociodemographic and psychobehavioral characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…One recent review concludes that so far there is limited evidence for a relationship between prehospital delay and knowledge of symptoms (Mooney et al, 2012 ). The correlation between type D personality especially for negative affectivity and prehospital decision delay was another finding of this research, although this phenomenon has already been reported before (Zhang et al, 2020 ). In our study, a mediating effect of type D personality in the relationship between job burnout and the prehospital delay was not found, indicating that certain personalities might have exerted a non-negligible effect in the delay independent of job fatigue.…”
Section: Discussionsupporting
confidence: 60%
“…One recent review concludes that so far there is limited evidence for a relationship between prehospital delay and knowledge of symptoms (Mooney et al, 2012 ). The correlation between type D personality especially for negative affectivity and prehospital decision delay was another finding of this research, although this phenomenon has already been reported before (Zhang et al, 2020 ). In our study, a mediating effect of type D personality in the relationship between job burnout and the prehospital delay was not found, indicating that certain personalities might have exerted a non-negligible effect in the delay independent of job fatigue.…”
Section: Discussionsupporting
confidence: 60%
“…Another study investigated the role of personality in AMI. It found that women with AMI and a type D personality (TDP) who have a tendency to experience negative emotions and to inhibit the expression of emotions, were generally less likely to delay seeking treatment compared to those without TDP (OR, 0.28; 95% CI, 0.08–0.98) [ 24 ]. However, depression may increase the delay in seeking treatment among participants with CHD [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This outcome suggests that while increasing knowledge might help reduce decision delays for males, alternative strategies may be necessary for females, who may face other gender-specific barriers. For instance, Zhang et al identified Type D personality—a tendency towards negative affectivity and social inhibition—as a possible risk factor for delayed medical help-seeking in ACS among females [ 34 ]. Arrebola-Moreno et al corroborated this, finding that Type D personality was linked to decision delays exclusively in females [ 35 ].…”
Section: Discussionmentioning
confidence: 99%